Evaluation of compressive strength and water absorption of soil-cement bricks manufactured with addition of pet (polyethylene terephthalate) wastes - Paschoalin Filho, João Alexandre; Storopoli, João Henrique; Guerner Dias, Antonio Jose (Acta Scientiarum. Technology, 2016)
This paper presents the evaluation of compressive strength of soil-cement bricks obtained by the inclusion in their mixture of PET flakes through mineral water bottles grinding. The Polyethylene Terephthalate (PET) has been characterized by its difficulty of disaggregation in nature, requiring a long period for this. On the other hand, with the increase in civil construction activities the demand for raw material also increases, causing considerable environmental impacts. In this context, the objective of this research is to propose a simple methodology, preventing its dumping and accumulation in irregular areas, and reducing the demand of raw materials by the civil construction industry. The results showed that compressive strengths obtained were lower than recommended by NBR 8491 (Associação Brasileira de Normas Técnicas [ABNT], 2012b) at seven days of curing time. However, they may be used as an alternative solution in masonry works in order to not submit themselves to great loads or structural functions. The studied bricks also presented water absorption near to recommended values by NBR 8491 (ABNT, 2012b). Manufacturing costs were also determined for this brick, comparing it with the costs of other brick types. Each brick withdrew from circulation approximately 300 g of PET waste. Thus, for an area of 1 m2 the studied bricks can promote the withdrawal of approximately 180 beverage bottles of 2 L capacity. Â